Analisis Perencanaan Biaya Proyek Pembangunan Gedung Undiksha Berbasis Building Information Modeling (BIM) - Arta, I Kadek Rio Parsana; Dharmastika, I Gusti Agung Gede Nodya; Eryani, I Gusti Agung Putu (Civil Infrastructure Engineering and Architectural Design, 2025)
One of the innovations that has received attention is Building Information Modeling (BIM). The software that applies the BIM concept is Autodesk Revit. This study compares the Cost Budget Plan (RAB) obtained through the BIM method, and the RAB calculated by conventional methods in the Denpasar Undiksha Campus Lecture Building Construction Project, to identify a more efficient method used in project cost estimation. The method used in this study is to collect project data in the form of structural work drawings, unit price analysis, and RAB, which is used as a reference for modeling with Autodesk Revit. The RAB calculated using the BIM method modeled on Autodesk Revit was obtained lower at IDR 3,003,134,274.71. while RAB was obtained from contract documents of IDR 3,425,386,712.44. The comparison between Autodesk Revit's RAB and the contract document RAB shows a difference of IDR 422,252,437.73 with an efficiency value of 12.33%. The Cost Budget Plan (RAB) generated through modeling using Autodesk Revit shows lower and more efficient values. This shows that the application of BIM methods in project cost planning can provide more accurate and optimal results